Clot waveform analysis in Clauss fibrinogen assay contributes to classification of fibrinogen disorders. Issue 174 (February 2019) - Suzuki, Atsuo; Suzuki, Nobuaki; Kanematsu, Takeshi; Shinohara, Sho; Arai, Nobuo; Kikuchi, Ryosuke; Matsushita, Tadashi
Abstract: Background: Clauss fibrinogen assay (CFA) is widely used as a screening test to detect fibrinogen disorders. However, CFA alone cannot distinguish quantitative and qualitative defects because it depends on functional fibrinogen activity (Ac), and fibrinogen antigen (Ag) determination is required to classify fibrinogen disorders. Objectives: To establish a novel approach to classify fibrinogen disorders, we investigated the potential of clot waveform analysis (CWA) of CFA and searched for a surrogate marker for fibrinogen Ag. Materials and methods: We analyzed CWA parameters obtained from CFA using plasma from normal patients (n = 91) and those with fibrinogen disorders (n = 27, including 15 hypofibrinogenemia, 6 dysfibrinogenemia and 6 hypodysfibrinogenemia) with a CS-5100 autoanalyzer. Results: We found that maximum coagulation velocity (Min1) levels were most strongly correlated with fibrinogen Ag in both normal and fibrinogen disorders. Hence, Min1 appeared to function as a surrogate for fibrinogen Ag. Although the Ac/Min1 ratio did not simply reflect the measured Ac/Ag ratio, we found that the Ac/Min1 ratio was significantly higher than normal in hypofibrinogenemia and hypodysfibrinogenemia, but not in dysfibrinogenemia. On the other hand, we could distinguish type II deficiency from type I using estimated fibrinogen Ag (eAg) predicted from Min1. The Ac/eAg ratios of dysfibrinogenemia and hypodysfibrinogenemia were significantly lower than those of normal and hypofibrinogenemia. Conclusion: The CWA of CFA could distinguish fibrinogen disorders using a combination of Ac/Min1 and Ac/eAg values. This analysis allows the qualitative detection of fibrinogen disorder easily and represents a novel screening test for fibrinogen disorders. Highlights: It is difficult to classify fibrinogen disorders by Clauss fibrinogen assay (CFA) alone. We developed clot waveform analysis (CWA) to distinguish fibrinogen abnormalities. We found the "Min1" value to be a surrogate marker for fibrinogen antigen. CWA of CFA could be a novel screening test for fibrinogen disorders.